Combination therapy with erythropoietin, magnesium sulfate and hypothermia for hypoxic-ischemic encephalopathy: an open-label pilot study to assess the safety and feasibility - Miho Nonomura; Sayaka Harada; Yuki Asada; Hisako Matsumura; Hiroko Iwami; Yuko Tanaka; Hiroyuki Ichiba (BMC, 2019)
Abstract Background Although therapeutic hypothermia improves the outcome of neonatal hypoxic-ischemic encephalopathy (HIE), its efficacy is still limited. This preliminary study evaluates the safety and feasibility of the combination therapy with erythropoietin (Epo), magnesium sulfate and hypothermia in neonates with HIE. Methods A combination therapy with Epo (300 U/kg every other day for 2 weeks), magnesium sulfate (250 mg/kg for 3 days) and hypothermia was started within 6 h of birth in neonates who met the institutional criteria for hypothermia therapy. All patients received continuous infusion of dopamine. Vital signs and adverse events were recorded during the therapy. Short-term and long-term developmental outcomes were also evaluated. Results Nine patients were included in the study. The mean age at first intervention was 3.9 h (SD, 0.5). Death, serious adverse events or changes in vital signs likely due to intervention were not observed during hospital care. All nine patients completed the therapy. At the time of hospital discharge, eight patients had established oral feeding and did not require ventilation support. Two patients had abnormal MRI findings. At 18 months of age, eight patients received a follow-up evaluation, and three of them showed signs of severe neurodevelopmental disability. Conclusion The combination therapy with 300 U/kg Epo every other day for 2 weeks, 250 mg/kg magnesium sulphate for 3 days and therapeutic hypothermia is feasible in newborn patients with HIE. Trial registration ISRCTN33604417retrospectively registered on 14 September 2018.